IMPRISONMENT FOR DOMESTIC VIOLENCE OFFENDERS WHO HAVE MEDIATED Review of Simalungun District Court Decision No. 19/PID. SUS/2019/PN Sim - Fitriani Fitriani (NOMOI Law Review, 2022)
Law No. 23 of 2004 on the Elimination of Domestic Violence provides a strong legal foundation that becomes domestic violence which was originally a domestic business into state affairs. For this reason, the thought arises of using penal mediation by seeking a win-win solution so that prison sentences must be avoided to the perpetrator so that the purpose of Article 4 letter d is achieved. Based on this can be formulated the problem in this paper is: what is the basis of the judge's consideration to impose a prison sentence on domestic violence offenders who have mediated in Decision No. 19 / PID. SUS/2019/PN Sim? The research methods used in this writing are normative juridical research methods or literature research methods. The results of the study showed that the imprisonment for 22 days to the perpetrator was very inappropriate, the opportunity to reconcile the domestic violence case in the District Court was open. Kuhap has provided an opportunity for judges to resuscitate offenders from prison. There are two provisions in the Kuhap that can be used as a legal basis for the implementation of penal mendiasi, namely Article 14A and Article 14 C, By using Article 14A, judges can prevent domestic offenders from prison sanctions by only giving a suspended sentence under one year until it does not need to be lived. And Article 14C to require perpetrators to cure violent behavior by undergoing counseling.Keywords: Prison, Offender, Domestic Violence, Mediation